Connecting stars and ionised gas with integral-field spectroscopy - McDermid, R; Emsellem, E; Shapiro, K; Bacon, R; Bureau, M; Cappellari, M; Davies, R; de Zeeuw, T; Falcon-Barroso, J; Krajnovic, D; Kuntschner, H; Peletier, R; et al. (2007)
Using integral-field spectroscopy, the SAURON survey has shown that early-type galaxies, once thought to be essentially devoid of gas, commonly show ionised gas emission. This emission is found with a rich variety of distributions and kinematics, ranging from very uniform disks or rings, and large-scale twisted structures, to flocculent and irregular streams. Such variety is missed in conventional long-slit spectroscopy, and integral-field spectroscopic data allow accurate removal of the underlying stellar continuum compared with imaging surveys, giving very low detection limits. Moreover, spectral data can simultaneously provide the stellar kinematics and populations as well as the emission-line properties. We investigate the connection between the stellar and gas properties using integral-field spectroscopy from SAURON, OASIS and GMOS, and find that, although some global trends exist, the connection between the stellar population parameters and the gas properties is in some cases puzzlingly unclear. (c) 2006 Elsevier B.V. All rights reserved.